2021
DOI: 10.4149/bll_2021_126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulse steroid therapy in patients critically ill with COVID-19

Abstract: OBJECTIVES: The aim of this study was to determine the effi cacy of pulse steroid therapy administered to patients critically ill with COVID-19 progressing into severe pneumonia. METHODS: A total of 600 patients included in this retrospective study were divided into three groups. Group 1 (control group): 200 patients who did not receive steroid treatment, Group 2: 200 patients who received dexamethasone 1x8 milligram (mg) or methylprednisolone 1x80 mg, Group 3: (pulse steroid therapy group): 200 patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…9 Our study results were consistent with a cohort study conducted by Ho et al in 2003, 10 which showed no differences in mortality or need for endotracheal intubation between PDS and NPDS in the management of patients with SARS. In this meta-analysis, we found similar results to those from a study by Gundogdu et al, 19 which showed that PDS and NPDS were associated with similar mortality (58.5% and 53.5%, respectively). Furthermore, our meta-analysis results remained consistent on subgroup analysis based on the strategy of PDS therapy (initial vs. rescue therapy).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…9 Our study results were consistent with a cohort study conducted by Ho et al in 2003, 10 which showed no differences in mortality or need for endotracheal intubation between PDS and NPDS in the management of patients with SARS. In this meta-analysis, we found similar results to those from a study by Gundogdu et al, 19 which showed that PDS and NPDS were associated with similar mortality (58.5% and 53.5%, respectively). Furthermore, our meta-analysis results remained consistent on subgroup analysis based on the strategy of PDS therapy (initial vs. rescue therapy).…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, we excluded 1558 studies because of the following: 1391 studies used inappropriate doses of steroids or lacked the appropriate comparison, 128 studies did not report data regarding the interventions of interest, and 39 studies were excluded due to lack of the appropriate outcomes of interest. Eventually, 10 studies met our inclusion criteria and were included in the meta‐analysis 14–19,22–25 . Figure 1 shows the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) flow chart that illustrates how the final studies were selected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations